2018
DOI: 10.1007/s00540-018-2504-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of acute neuroinflammation in postoperative delirium-like cognitive deficits in rats

Abstract: Our findings indicate that surgery-induced acute, transient, brain-wide neuroinflammation may be involved in the pathogenesis of the postoperative delirium-like cognitive deficits in rats. Furthermore, neuroinflammation may convert from acute to chronic in an age- and hippocampal-specific manner, likely resulting in the development of sustained cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…However, TNF‐α was also increased after anesthesia without surgery, but no activation of microglia was found in the hippocampus. It suggests that isoflurane anesthesia alone could not induce harmful inflammation in the hippocampus, which is in line with Wang et al and Kawano et al’s findings 32,33 . Callaway et al 34 and Crosby et al 35 demonstrated that exposure to sevoflurane or isoflurane alone had no impact on learning and memory in the rodent.…”
Section: Discussionsupporting
confidence: 72%
“…However, TNF‐α was also increased after anesthesia without surgery, but no activation of microglia was found in the hippocampus. It suggests that isoflurane anesthesia alone could not induce harmful inflammation in the hippocampus, which is in line with Wang et al and Kawano et al’s findings 32,33 . Callaway et al 34 and Crosby et al 35 demonstrated that exposure to sevoflurane or isoflurane alone had no impact on learning and memory in the rodent.…”
Section: Discussionsupporting
confidence: 72%
“…A recent study suggested the involvement of neuroinflammation in postoperative delirium-like cognitive deficits [13]. We tested whether propofol could impact the expression level of IL-6 in the brain tissues of these mice.…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies, research has shown that surgery increases the risk of cognitive impairment when compared with exposure to anesthesia alone [69, 70]. One study established a model of abdominal surgery under local anesthesia alone to assess the effects of surgery without the confounding risk of sedative or anesthesia exposure.…”
Section: Main Bodymentioning
confidence: 99%
“…In animal studies, there is mixed evidence regarding whether volatile agents increase pro-inflammatory cytokines and/or microglial activation in the absence of surgery. Although an increase in inflammation has been observed by some groups [75, 103105], other groups have reported no effect of isoflurane or sevoflurane anesthesia alone on microglial activation and/or proinflammatory cytokine expression [70, 82, 106, 107]. The mechanism for induction of neuroinflammation following exposure to anesthesia with or without surgery continues to be actively investigated.…”
Section: Main Bodymentioning
confidence: 99%